2018
DOI: 10.1126/sciadv.aat1808
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of soil bacteria and archaea across France

Abstract: Each soil bacterial taxon exhibits a specific wide scale distribution explained by particular environmental filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
155
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 62 publications
(117 reference statements)
15
155
2
2
Order By: Relevance
“…The genus Mycobacterium is ubiquitous and reasonably abundant in soil as determined by our cultivation-independent 16S rRNA gene analyses. We found that Mycobacterium was typically one of the more abundant named genera of bacteria found in soil, confirming results reported in comparable studies (13, 19, 21). However, the relative abundance of mycobacteria was highly variable across soils ranging from 0.03 to 2.9% of 16S rRNA gene reads, a range similar to that reported previously (1921).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The genus Mycobacterium is ubiquitous and reasonably abundant in soil as determined by our cultivation-independent 16S rRNA gene analyses. We found that Mycobacterium was typically one of the more abundant named genera of bacteria found in soil, confirming results reported in comparable studies (13, 19, 21). However, the relative abundance of mycobacteria was highly variable across soils ranging from 0.03 to 2.9% of 16S rRNA gene reads, a range similar to that reported previously (1921).…”
Section: Discussionsupporting
confidence: 92%
“…Members of the Mycobacterium genus are commonly detected across a broad range of soil types using both cultivation-dependent and cultivation-independent methods. We know from cultivation-independent surveys of soil bacterial communities that mycobacteria are nearly ubiquitous in soil and the genus Mycobacterium is consistently one of the more abundant genera of soil bacteria, ranging in relative abundance from ~0.5-3.0% of the total community (1921). For instance, the Mycobacterium genus has been detected in soils from bogs (22), forests (13, 23, 24), croplands (25, 26) and livestock farms (2729), and even in potting soil (30).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterivores and eukaryvores were differentially influenced by three edaphic factors, i.e. pH, texture and organic carbon content (Figure 4), the very same major drivers of bacterial community structure at national and continental scales (Bahram et al, 2018;Karimi et al, 2018;Plassart et al, 2019).…”
Section: Opposite Responses Of Trophic Guilds In Forestmentioning
confidence: 99%
“…Large-scale spatial variation in the composition of the soil biota has been associated with difference in edaphic and climatic conditions 9 . Particularly, local edaphic factors such as soil pH primarily predict geographic distribution of soil bacteria 10, 11, 12 , whereas climatic variables better predict fungal distribution in soil 13 . However, systematic field studies exploring and disentangling the extent to which variation in soil and climatic conditions impacts root microbiota composition and adaptive differentiation in plants are lacking.…”
Section: Introductionmentioning
confidence: 99%